Morph-specific selection drives phenotypic divergence in color polymorphic tawny owls (Strix aluco) in Northern Europe - Passarotto, Arianna; Lürig, Moritz David; Aaltonen, Esa; Karell, Patrik (Communications Biology, 2026)
There is a long tradition in using genetically based color polymorphisms in natural populations to study evolutionary processes. Despite growing evidence for continuous phenotypic variation within discrete morphs, we still know little about how this shapes selective dynamics. Here, using 43 years of plumage color data from a Finnish tawny owl population (Strix aluco), we show that gray and brown morphs exhibit substantial intra-morph variation, which has diverged over time. Plumage in the brown morph became increasingly pigmented, while the gray morph showed an abrupt shift toward lighter coloration. By examining both adult and offspring plumage, we identified morph-specific drivers of these trends: in gray owls, reduced pigmentation appears linked to extreme winters that eroded standing genetic variation, likely constraining their evolutionary response. In contrast, brown morph dynamics were shaped by an interaction between plumage coloration, reproductive success, and breeding timing, along with stronger temperature effects during the pre-fledging period. These findings suggest that intra-morph variation determines each morph’s response to selection pressures, potentially influencing their ability to track shifting phenotypic optima. Our work highlights the relevance of phenotypic variation within genetically discrete morphs for evolutionary processes, including how populations respond to environmental change.